Tax Accounting for The Renewable Energy (Electricity) Act 2000: A Tax by Any Other Name Would Smell as Sweet - Fullarton, Lex; Davies, Brett (Thomson Reuters (Professional), 2024)
Australia has committed to reducing greenhouse gas emissions, and part of that commitment is the enactment of the Renewable Energy (Electricity) Act 2000 (Cth) (the REE Act). This article focuses on the Australian renewable Energy Target and how the REE Act impacts on the electrical generation industry to dilute greenhouse gas emissions. The research examines the market of trading ‘carbon credits’ produced under the provisions of the REE Act, which are known as Renewable Energy Credits (RECs), and views this as a taxation and subsidisation system. It aims to develop a clear understanding of the operations of the REE Act: how the REC system interacts with Australia’s two other main taxes – Income Tax and Goods and Services Tax; and how the trade in RECs may be treated in the accounts of the respective trading entities – the liable parties and the renewable energy electricity generators.